2011
DOI: 10.1088/0957-4484/22/27/275605
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous synthesis of internally doped Cu:ZnSe/ZnS core–shell nanocrystals with good stability

Abstract: To prepare biologically available Zn-based NCs in aqueous solution, we herein reported the synthesis of aqueous Cu:ZnSe/ZnS NCs with internally doped aqueous Cu:ZnSe NCs as the core template. Due to the dual protection of Cu impurities by the ZnSe core and ZnS shells, the as-prepared Cu:ZnSe/ZnS NCs show excellent stability in the open air, which overcomes the intrinsic instability of traditional aqueous Cu:ZnSe NCs. The as-prepared Cu:ZnSe/ZnS NCs possess extremely good stability, good biocompatibility and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…For PL peak around 480 nm, the stokes shift is as large as 100 nm, which indicated surface defect related emission. This PL characteristic of water soluble ZnSe NCs and ZnSe:Cu was reported by earlier publications [28,31]. Once addition of Cu stock solution into ZnSe solution, the emission of ZnSe NCs changed immediately, indicating the extremely fast cation exchange reaction.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…For PL peak around 480 nm, the stokes shift is as large as 100 nm, which indicated surface defect related emission. This PL characteristic of water soluble ZnSe NCs and ZnSe:Cu was reported by earlier publications [28,31]. Once addition of Cu stock solution into ZnSe solution, the emission of ZnSe NCs changed immediately, indicating the extremely fast cation exchange reaction.…”
Section: Resultssupporting
confidence: 83%
“…NaHSe solution was prepared by using Se and NaBH 4 according to the reference methods [28,29]. Aqueous ZnSe NCs were synthesized according to the reference method [30,31].…”
Section: Synthesis Of Znse Ncsmentioning
confidence: 99%
“…In a previous study , we investigated the mechanism behind the weak stability of Cu:ZnSe QDs and reported the first example of aqueous Cu:ZnSe/ZnS QDs with excellent stability . The key to excellent stability in as‐prepared QDs is the simultaneous preparation of core–shell QDs and internally doped impurities.…”
Section: Introductionmentioning
confidence: 99%
“…This huge disadvantage makes these internally doped water-soluble Cu:ZnSe QDs impossible to apply in biology. Then, we reported the first example of water-soluble Cu:ZnSe/ZnS QDs with excellent stability [6]. The key for the excellent stability of as-prepared QDs is attributed to the simultaneous preparation of core-shell QDs and internally doped impurities.…”
Section: Introductionmentioning
confidence: 99%